Related Factors With The Event Of Less Chronic Energy In Pregnant Women - Nurdika Parsya; Edison Siringoringo; Asnidar; Tenriwati (Jurnal Life Birth, 2020)
Chronic energy deficiency (KEK) is a state of malnutrition in unfavorable conditions. The need for pregnant women will increase from the usual exchange of almost all very active loads, especially in the third trimester. Therefore, an increase in the amount of food consumption needs to be increased, especially the consumption of food sources of energy to meet all the needs of the mother & fetus, so if a little consumption will cause malnutrition or usually called KEK. The research objective was to determine the factors associated with the less chronic incidence in pregnant women. This research is a quantitative study, conducted with a descriptive-analytic, using a cross-sectional study approach. Cross-section design. The research sample was 44 respondents with Fisher's test. The results of this study indicate that there is a relationship between knowledge and the incidence of KEK in pregnant women using Fisher's test, the p-value is 0.004 (p <0.05). , 05), there is no relationship between parity and SEZ occurrence using Fisher's test, the p-value is obtained at 0.533 (p> 0.05). The conclusion in this study is that there is a relationship between knowledge and economic level with the incidence of KEK, there is no relationship between parity and the incidence of KEK in pregnant women. Suggestions for research to further expand the research sample not only to focus on pregnant women, but researchers can also examine adolescents and also pregnant women who experience chronic energy deficiency add research variables such as those that have not been researched, namely factors from disease infections and sources of disease. related to the incidence of KEK, Increasing the research period, with a longer period and it is hoped that more accurate and unusual research results can be obtained.